Polycythemia Vera Presenting as Tinnitus and Hearing Loss: A Case Report - Thong, How Kit; Goh, Kim Yen; Bin Saim, Aminuddin (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Polycythemia vera (PV) is a chronic myeloproliferative neoplasm (MPN) characterized by erythrocytosis and commonly associated with the JAK2 V617F mutation. PV is a relatively rare disease with a prevalence rate of 22 per 100,000. Historically, hearing impairments were first described as a complication of PV in 1963, and it was stated that symptoms recovered after a phlebotomy. Occlusion and thrombosis of the feeding labyrinthine artery causing cochlear ischemia were thought to be the cause of such symptoms and complaints. CASE PRESENTATION: We are reporting a case of PV that was presented in our ENT outpatient clinic. The patient presented with a main complaint of sudden-onset bilateral tinnitus with one-sided hearing loss. The patient was treated medically with hydroxyurea, aspirin, and phlebotomy. On improvement of the hematological parameters, the patient noted an improvement in his hearing and it was confirmed with the finding on the repeated hearing assessment. CONCLUSION: This case emphasizes the importance of otolaryngologists remaining vigilant and maintaining a high index of suspicion as PV can present with audiological symptoms. The early diagnosis and initiation of treatment can improve patients’ hearing and reduce the morbidity of such patients.